2016
DOI: 10.1111/nyas.13191
|View full text |Cite
|
Sign up to set email alerts
|

The role of progranulin in arthritis

Abstract: Progranulin (PGRN) is a growth factor with a unique beads-on-a-string structure that is involved in multiple pathophysiological processes, including anti-inflammation, tissue repair, wound healing, neurodegenerative diseases, and tumorigenesis. This review presents up-to-date information concerning recent studies on the role of PGRN in inflammatory arthritis and osteoarthritis, with a special focus on the involvement of the interactions and interplay between PGRN and tumor necrosis factor receptor (TNFR) famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
47
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 158 publications
(366 reference statements)
0
47
0
Order By: Relevance
“…OA is considered to be a degenerative disease characterized by cartilage destruction, subchondral bone sclerosis, synovium inflammation, and osteophyte formation (37). Even though it is well-accepted that cartilage, plasma and synovial fluid CTGF concentrations positively correlate with radiographic severity in osteoarthritis patients (38), studies that have indicated a role of CTGF in osteoarthritis are controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…OA is considered to be a degenerative disease characterized by cartilage destruction, subchondral bone sclerosis, synovium inflammation, and osteophyte formation (37). Even though it is well-accepted that cartilage, plasma and synovial fluid CTGF concentrations positively correlate with radiographic severity in osteoarthritis patients (38), studies that have indicated a role of CTGF in osteoarthritis are controversial.…”
Section: Discussionmentioning
confidence: 99%
“…CTGF is a well-studied protein in arthritis; however, its roles in osteoarthritis (OA) and inflammatory arthritis differ. OA is considered to be a degenerative disease characterized by cartilage destruction, subchondral bone sclerosis, synovial inflammation, and osteophyte formation (37). Even though it is well accepted that cartilage, plasma, and synovial fluid CTGF concentrations positively correlate with radiographic severity in OA (38), studies have yielded conflicting results regarding its role in this disease.…”
Section: Discussionmentioning
confidence: 99%
“…Second, one needs to quantify entangle-ment in order to go beyond the simple entangled vs. separable scheme [2]. A popular way to quantify multiparticle entanglement makes use of the geometric measure of entanglement [3]. For that, one defines for pure states via…”
Section: Introductionmentioning
confidence: 99%
“…This is a typical method to extend a pure state entanglement measure to the mixed state case, but obviously this minimization is difficult to perform. So far, only in some special cases the evaluation of the geometric measure for mixed states is possible [3,8,9]. Analytical results on the evaluation of the convex roof for other measures have to date mainly be obtained for the bipartite measure of the concurrence and measures with a related mathematical structure [10].…”
Section: Introductionmentioning
confidence: 99%
“…The precursor protein is proteolytically processed by elastase into individual granulin modules, which each have masses in the 6 kDa range, after secretion from the cell . PGRN has similar activities to granulin including roles in cellular proliferation, controlling embryogenesis, tissue repair, cancer, and inflammation …”
Section: Introduction—granulinsmentioning
confidence: 99%